Feasibility study on implementation of marine renewable energy in Malaysia by considering the project costs and urban public acceptance / Lim Xin Le - Lim, Xin Le (2015)
Energy demand due to increasing global population and the need for low carbon energy have led to the rising importance of renewable energy. Apart from the three most used renewable energy sources in Malaysia – solar energy, hydroelectric and biomass –marine renewable energy may be another potential player in the renewable energy market. Marine renewable energy, which comprises of tidal energy, wave energy, ocean thermal energy conversion (OTEC) and salinity gradient, can be harnessed in Malaysia as the country is surrounded by abundant water resources. The development of marine renewable energy, however, is currently still in its infancy and may face economical and societal challenges in its implementation. Clean Development Mechanism (CDM) and Feed-in Tariff (FiT) are believed to be the crucial driving forces for the marine renewable energy market as the mechanisms bring monetary profits to the investors. Profits earned through CDM and FiT system are expected to reduce the project cost of marine renewable energy. This study is aimed at examining the feasibility and to push forward the development of marine renewable energy in Malaysia. There are three parts in this study. First, the investigation of the implementation of renewable energy projects in Malaysia which is registered in CDM. Second, the proposal of reasonable FiTs for marine renewable energy. The third part of this study is to gauge the level of public acceptance of marine renewable energy, as it is crucial information to be known prior to the commencement of project. Data collections through literatures and interviews were done to complete the first part. The second part is achieved by proposing appropriate FiT rates for marine renewable energy based on Net Present Value approach, which are then validated by comparing with the implemented FiT in other countries. In the third part, a survey on public acceptance of marine renewable energy was conducted in SS2, Petaling Jaya and the data collected was analysed using SPSS. As a result, it is worth noting that 69% of the CDM projects are related to renewable energy. 102 local energy-